Effect of concentration and exposure period to butyrolactone I on meiosis progression in bovine oocytes - Adona,P.R. (2006)
The effect of concentration and exposure period of bovine oocytes to butyrolactone I (BLI) on meiotic block and in vitro maturation (IVM) kinetics was studied. In experiment 1, all oocytes were at germinal vesicle stage (GV), after 6h in culture with 0, 50 and 100µM BLI. After 12h, all oocytes cultured with 50 and 100µM BLI remained in GV. After 24h, less oocytes were in GV with 50µM (82%) than with 100µM BLI (99%, P<0.05). In experiment 2, after 6h IVM, 93% of control oocytes (IVM only) were in GV, while treated oocytes (100µM BLI for 6, 12 or 24h prior to IVM) showed less oocytes in GV with increased exposure period to BLI prior to IVM (83 and 73%, for 6h and 12h, P<0.05). For a 24h inhibition, GV rates were similar to 12h (70%, P>0.05). After 18h IVM, metaphase II (MII) rates were similar for all groups (76-81%). In experiment 3, after 6h IVM, 74% of treated oocytes (50 or 100µM BLI for 12h) were in GV. This rate was lower than for control oocytes (97.3%, P<0.05). After 18h IVM more oocytes (~80%, P>0.05) were in MII with BLI than for control (73%, P<0.05). Shorter culture periods require lower BLI concentration for meiotic block; initial nuclear maturation kinetics of oocytes cultured with BLI is accelerated, and this is affected by culture period but not by drug concentration.